2018
DOI: 10.1002/jccs.201800292
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, reactions, and biological study of some new thienopyrimidine derivatives as antimicrobial and anti‐inflammatory agents

Abstract: Pyrimidine and thienopyrimidine derivatives play a very important role in organic chemistry because of their wide applications as bioactive compounds with multiple biological activities. However, a literature survey revealed that the merger of different groups in the thieno[2,3-d]pyrimidine heterocyclic ring enhances its antibacterial, antifungal and anti-inflammatory activities. This encouraged us to prepare a new series of thieno[2,3-d]pyrimidine heterocyclic compounds and to test them as antimicrobial and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Furthermore, thienopyrimidines have anticipated biological activity . In the light of the previous biological importance and in our ongoing endeavor to create new pyrazole thienopyrimidine‐based hybrids, we have synthesized here a series of new heterocyclic compounds isoindole, pyrazole, and triazepine attached or fused to the pyrazolothienopyrimidine ring system. Subsequently, due to the resistance of most bacterial and fungal strains to the current antimicrobial therapy, we are interested in synthesizing more effective agents.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, thienopyrimidines have anticipated biological activity . In the light of the previous biological importance and in our ongoing endeavor to create new pyrazole thienopyrimidine‐based hybrids, we have synthesized here a series of new heterocyclic compounds isoindole, pyrazole, and triazepine attached or fused to the pyrazolothienopyrimidine ring system. Subsequently, due to the resistance of most bacterial and fungal strains to the current antimicrobial therapy, we are interested in synthesizing more effective agents.…”
Section: Introductionmentioning
confidence: 99%
“…1 H NMR spectrum of 2b displayed a D 2 O exchangeable singlet at δ = 6.72 ppm for NH 2 ; in addition to a singlet at δ = 2.90 ppm for the pyrimidine CH 3 , while the furan H appear as multiplet signals in the region δ = 6.83-7.97 ppm. Its 13 C NMR showed one sp 3 signal at δ = 24.16 ppm for CH 3 ; in addition to the other expected sp and sp 2 signals. Also, IR spectrum clarified absorption bands at 3327, 3228, 2197 cm −1 for NH 2 and C N functions, respectively.…”
Section: Resultsmentioning
confidence: 92%
“…This result was confirmed by 1 H NMR, which displayed two new singlets at δ = 3.40 and 12.93 ppm for CH 2 CN and NH. Also, its 13 C NMR spectrum showed two sp 3…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Among all fused thienoazines, pyridothienopyrimidine derivatives have been studied the most. These derivatives act as bactericides 2−6 fungicides, 2−6 antiprotozoals, 7 or immunomodulators; exhibit antianaphylactic, antiallergic, 8 anticonvulsive, 9 analgetic, or anti-inflammatory activities; 10,11 and are used as intermediate products in chemical pharmaceutical industry. 1 In addition to antimicrobial, 2−6 anticonvulsant, 9 and anticancer activities 12−17 of pyridothienopyrimidine deriva-tives, recent studies showed that they have the ability to specifically activate testicular steroidogenesis without affecting thyroid functions.…”
Section: ■ Introductionmentioning
confidence: 99%